Sources of naked oat for grain quality breeding - G. A. Batalova; N. V. Krotova; E. N. Vologzhanina; O. A. Zhuikova; G. P. Zhuravleva; M. V. Tulyakova (Аграрная наука Евро-Северо-Востока)
Ninety-eight varieties of naked oat were studied in Federal Agricultural Research Center of the North-East (Kirov. Kirov region) in 2012 - 2017. Growth conditions differed in years. the sum of active temperatures from May till August varied from 1135° in 2017 to 1632° in 2016. Studies were conducted according to Methodical directions on study of barley and oat world collection (2012). Estimation of grain quality (content of protein and fat) was done with the use of INFRAMATIC 8620 system. The released naked variety Vyatsky was the standard. Productivity of naked oat samples in 2017 varied from 111 to 511 g/m2 and had an average value of 300 g/m2. The variety 282h09 (Russia) had maximal productivity (149%), an average level for the whole period of studies being 283 g/m2 (80.6 % to standard). High stability of production (average 311 g/m2 or 95% to standard) and grain quality (protein content 15.57%) raised the possibility of using the variety PZS-LYM-03 (China) for creation of productive oat genotypes with high grain quality. There were selected 38 sources of naked oat including those having minimal amount of husked grains in yield (0.1.. .0.9 %) - 358h10 (Russia), BAYS -159 (Belarus), BAI 6057, BAI 6105, 15149 local (China), 15091 MF 9224-336, 15158 MF 9224-359 (USA); having high grain protein (15.91.16.12 %) - 15089 MF 9224-106, MF 9224-247, MF 9521-281 (USA) and fat (4.35 %) - 15094 MF 9521-247 (USA). Varieties with higher protein content had lower fat content and vice versa. Larger amount of husked grains in yield was noted in years with higher temperatures during the period from ear emergence to wax maturity and at abundant precipitations during the period from sowing till shooting.